Alkaloids from Fissistigma fulgens Merr. Annonaceae) - A. Hadi, A. Hamid (Malaysian Journal of Science, 2000)
A study on the alkaloids of Fissistigma fulgens Merr. was performed. Five alkaloids have been isolated from this species, i.e liriodenine, anonaine, argentinine, discretamine and kikemanine. Discretamine and kikemanine belong to the protoberberine type of alkaloids.